TA Treatment of Depression: A Hermeneutic Single-Case Efficacy Design Study - Sergio - Enrico Benelli (International Journal of Transactional Analysis Research, 2018)
This study is the fifth of a series of seven and belongs to the second Italian systematic replication of findings from previous series that investigatedthe effectiveness of a manualized Transactional Analysistreatment for depression through Hermeneutic Single-Case Efficacy Design.The therapist was a white Italian woman with 5years of clinical experience and the patient, Sergio, was a 39-year old white Italian man who attended sixteen sessions of transactional analysis psychotherapy. Sergio satisfied DSM 5 criteria for Persistent Depressive Disorder (Dysthymia) with melancholic features, Post-Traumatic Stress Disorder (PTSD) with Obsessive Personality traits. The treatment focused on the permission to enjoy and on self-protection. The focus on both depressive symptoms and obsessive traits allowed a remission of his dysthymia within the end of therapy. The judges evaluated the case as a good outcome: the depressive and anxious symptomatology clinically and reliably improved over the course of the therapy and these improvements weremaintained at the followups. Furthermore, the patient reported significant change in his post-treatment interview and these changes were directly attributed to the therapy. Citation - APA format: